PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU SMA YADIKA 3 KARANG TENGAH - Riesminingsih Riesminingsih (Universitas Mercu Buana, 2013)
Abstract: The research aims to determine the influence of teacher’s competency andMotivation to the teacher’s performance in Yadika 3 Senior High School.The variables’research are Competency And Motivation to analyze the influence of Teacher’sPerformance as the samples through questioner by using ordinal scale with saturationtechnique for the total amount of Yadika 3 Senior High School’ teachers are 63 people.Using Multiple Linier Regression analysis to analyze data. The result of statisticaldescriptive analysis shows that Competency, Motivation and teacher’s performance inYadika 3 Senior High school are High. The result of hypothesis’ test conclude that thereare influence which positive and significant between Competency, Motivation either byitself and also in common.Keywords: Competency, Motivation, Teacher’s performance